Registered Accommodation in Łódź 1979-2000 - Matczak, Andrzej (Turyzm/Tourism, 2002)
The author attempts to evaluate the take up of registered accommodation outlets in Lôdz between 1979 and 2000, on the basis of an analysis of changes in the number of guests, the number of accommodation outlets used, the average length of time spent in them, the average length of stay, and seasonality, sex, age, educational and professional background of the guests, their motives for coming to Lôdz, as well as the areas they arrived from.